The Needs Analysis of the Android-based Online Psychological Assessment Applications Usage for School Counselors in West Sumatra - Ardi, Zadrian; Jasril, Ilmiyati Rahmy; Yendi, Frischa Meivilona; Yuca, Verlanda (Universitas Negeri Padang, 2021)
Psychological assessment for students is one of the activities that cannot be separated from counseling services. Psychological attributes obtained from the implementation of the assessment can be used by school counselors to intervene and develop counseling programs. However, conditions in the field indicate that school counselors still have not carried out a comprehensive assessment of the condition of students, so this has an impact on the effectiveness of counseling services. This research and community service aims to provide training and skills for school counselors in conducting psychological assessments using an Android application called Potential. The urgency of using this application has increased since the emergence of the Covid-19 pandemic, where students and school counselors cannot meet face-to-face. This community service is carried out in stages in a series of workshops and independent training. School counselors are provided with a Potential account that can be used at their school. The results of community service activities show that students' psychological conditions are generally mapped through applications and assist school counselors in planning and developing effective programs.